Since a+a=a+b, a must = b
so 2(a-b) would be 2(0) while a-b would also be 0, so:
2(a-b)=a-b
2(0)=0
0=0
the last one isnt true.
don't question my God question your math skills.
or lack thereof.
explain to me where -2b went and i'll explain to you where God is
-2b just can't disappear.
what happened to -2b?
[chicka][chicka][chicka]
last is faked! asd
you can't divide by 0...-2b didn't go anywhere....b-2b=-b
fail... a-b = 0 as stated by the first equation...
Since a+a=a+b, a must = b
so 2(a-b) would be 2(0) while a-b would also be 0, so:
2(a-b)=a-b
2(0)=0
0=0
the last one isnt true.
don't question my God question your math skills.
or lack thereof.
explain to me where -2b went and i'll explain to you where God is
-2b just can't disappear.
what happened to -2b?
[chicka][chicka][chicka]
last is faked! asd
you can't divide by 0...-2b didn't go anywhere....b-2b=-b
fail... a-b = 0 as stated by the first equation...